Cognitive trajectories: exploring the predictive role of subjective cognitive decline and awareness of age-related changes for cognitive functioning - Sabatini, Serena; Cosentino, Stephanie; Chapman, Silvia; Ballard, Clive; Brooker, Helen; Corbett, Anne; Stephan, Blossom C. M. (Frontiers in Psychiatry, 2023)
Background: We investigated whether aspects of subjective cognitive aging, including awareness of age-related gains and losses in cognition (AARC-gains, AARC-losses) and subjective cognitive decline (SCD), predict change in objective cognitive function as measured by verbal reasoning (VR) and working memory (WM). Methods: We used longitudinal data for 3299 cognitively healthy UK residents aged 65+. We used data on AARC and SCD assessed in 2019, and cognitive tasks assessed in 2019, 2020, and 2021. We used latent growth curve modelling, latent class growth analysis, and growth mixture modelling. Results: For VR, multiple growth trajectories were not evident. Mean VR at baseline was 37.45; this remained stable over time. Higher AARC-gains in cognition (mean intercept= -0.23; 95%CI: -0.31; -0.16), higher AARC-losses in cognition (mean intercept= -0.37; 95%CI: -0.46; -0.28), and lower SCD (mean intercept= 2.92; 95%CI: 2.58; 3.58) were associated with poorer VR at baseline. A three-class growth mixture model-class varying best represented trajectories of WM. In Class 1 (N=182) mean WM at baseline was 31.20; this decreased by 2.48 points each year. In Class 2 (N=119) mean WM at baseline was 23.12; this increased by 3.28 points each year. In Class 3 (N=2998) mean WM at baseline was 30.11; and it remained stable. Higher AARC-gains (Odds Ratio= 1.08; 95%CI: 1.03; 1.14) and AARC-losses (Odds Ratio= 1.10; 95%CI: 1.04; 1.16) in cognition predicted greater likelihood of being in Class 2 than Class 3. Conclusions: Although both higher AARC-gains and AARC-losses indicate poorer concurrent cognition, higher AARC-gains may be a resource that facilitates future cognitive improvement.